Emerging Role of PACAP as a New Potential Therapeutic Target in Major Diabetes Complications - Rubina Marzagalli; Soraya Scuderi; Filippo Drago; James A. Waschek; Alessandro Castorina (International Journal of Endocrinology)
Enduring diabetes increases the probability of developing secondary damage to numerous systems, and these complications represent a cause of morbidity and mortality. Establishing the causes of diabetes remains the key step to eradicate the disease, but prevention as well as finding therapies to ameliorate some of the major diabetic complications is an equally important step to increase life expectancy and quality for the millions of individuals already affected by the disease or who are likely to develop it before cures become routinely available. In this review, we will firstly summarize some of the major complications of diabetes, including endothelial and pancreatic islets dysfunction, retinopathy, and nephropathy, and then discuss the emerging roles exerted by the neuropeptide pituitary adenylate cyclase activating polypeptide (PACAP) to counteract these ranges of pathologies that are precipitated by the prolonged hyperglycemic state. Finally, we will describe the main signalling routes activated by the peptide and propose possible future directions to focus on developing more effective peptide-based therapies to treat the major complications associated with longstanding diabetes.